(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Adoption of QR Code Indonesian Standard (QRIS) technology can simplify payment transactions and improves MSMEs’ efficiency. However, QRIS has not been fully adopted by MSMEs in Indonesia, reflected by a relatively low adoption rate. Therefore, this study uses the Technology, Organization, Environment (TOE) framework to analyse the influence of TOE factors on QRIS adoption and the impact on the MSMEs performance. This study used questionnaires gathered from 299 MSMEs in Indonesia and Structural Equation Modeling (SEM) approach to assess the hypotheses. The findings show that the adoption of QRIS is determined by organisational and environmental factors, while technological factors have no significant effect. Furthermore, this study proves that QRIS adoption has a significant impact on the MSMEs performance. Based on the findings, this study suggests the importance of collaboration between regulators and Payment Service Providers to provide education and assistance to MSMEs to increase the adoption of QRIS.